Dysphagia Management in Children: Implementation and Perspectives of Flexible Endoscopic Evaluation of Swallowing (FEES) - Athanasia Printza; Katerina Sdravou; Stefanos Triaridis (MDPI AG, 2022)
Dysphagia is any impairment of swallowing that compromises the safety, efficiency, or adequacy of nutritional or liquid intake. It is common in children, especially in some clinical populations, and may result in failure to thrive and respiratory problems due to pulmonary aspiration. Swallowing disorders have a severe impact on children's health, growth, and development, and on the quality of life of the child and family. Clinical evaluation cannot validly predict aspiration, which is mostly silent. A team management approach is advocated, including instrumental swallowing assessments. FEES has been proven to be safe and valid and is increasingly used in children of all ages. It allows the identification of structural abnormalities, assessment of the child's diet with real-life food and liquids while the child holds the optimal or preferred position, examination during breastfeeding, and assessment of fatigue and treatment strategies. FEES is carried out following a protocol that comprises three parts: the evaluation of the anatomical and physiological parameters of swallowing, testing of food and liquids of a range of different consistencies, and evaluation of treatment methods. Pediatric FEES involves adaptations for infants, and special considerations about readiness for nutritive trials and the infant's ability to sustain a coordinated feeding pattern. Varying consistencies and volumes of food or liquids are tried. Care of the dysphagic child involves team work. FEES, as a part of the assessment and management of dysphagia, enables the evaluation of the safety, efficiency, and adequacy of oral food and liquid intake. Future perspectives include standardized training in clinical FEES protocols to ensure clinical competency of the pediatric FESS team members and the development and validation of standardized examination and interpretation protocols for pediatric FEES.